Chinese Medicine: A Novel Therapeutic Option for Pancreatic Cancer - Yan, Ping; Cao, Yongxing; Sun, Xiaotian (Current Signal Transduction Therapy, 2014)
Pancreatic cancer is one of the most common human cancers with very low survival rate. So far, the difficulties to make early diagnosis and find curative therapy for this malignant disease remain challenging. Considering Chinese medicine with a long history of clinical application in treating various human diseases, it has been now introduced into the anti-cancer treatment and begun to attract attentions of researchers worldwide. Here, we summarize the recent studies on the anti-tumor activity of Chinese medicine in human pancreatic cancer and the potential molecular mechanisms.
Keywords: Chinese medicine